Dynamics of Work Ethic, Work Environment, and Organizational Culture in Encouraging Employee Performance - Waluyo, Budi; Sutianingsih, Sutianingsih (International Journal of Economics, Business and Accounting Research (IJEBAR), 2025)
This study aims to analyze the influence of work ethic, work environment, and organizational culture on employee performance at the Regional Finance Agency (BKD) of Boyolali Regency. This quantitative research uses a census approach by involving the entire population of Boyolali BKD employees totaling 110 people as respondents. Data were collected through questionnaires using a Likert scale of 1-5 and analyzed using the Partial Least Square-Structural Equation Modeling (PLS-SEM) method with the help of SmartPLS software. The results of the study show that work ethic, work environment, and organizational culture significantly and positively affect employee performance. Based on these findings, it is concluded that these three variables are important factors in improving employee performance at BKD Boyolali. Therefore, it is recommended to all employees to continue to strengthen their work ethic, create a conducive work environment, and internalize a positive organizational culture to achieve optimal performance.